Quality of Outpatient Care in Lebanon: A Cross-Sectional Survey - Georges Choueiry; Anna Maria Henaine; Rayan Darwish; Pascale Salameh (Patient Experience Journal)
Patient experience is an important driver of healthcare improvement. Yet, in Lebanon, there is a lack of studies focusing on the satisfaction of outpatients with healthcare quality. This study aims to assess the quality of outpatient care in Lebanon from the patient’s perspective and identify its determinants. A cross-sectional survey was administered, between December 2023 and January 2024, to 265 participants over 18 years old who consulted a healthcare provider, excluding dentists. We used linear regression to determine factors affecting consultation quality as perceived by the participants. Waiting time before consultations typically ranged from 5 to 15 minutes, the average consultation duration was 20.8 minutes, and the average quality rating of consultations was 8.3/10. Overall, patients expressed satisfaction with the waiting time, physician and staff behavior, outcomes, and instructions received. Up to 40% of the variance in perceived quality could be attributed to physician-modifiable factors, such as friendliness (β = 0.5, p = 0.53), listening skills (β = 0.7, p = 0.14), attentiveness and effort (β = 0.9, p = 0.04), patient comfort (β = 2.3, p < 0.01) and privacy (β = -0.1, p = 0.82), acceptable consultation duration (β = 0.6, p = 0.12), fewer interruptions (β = 0.7, p = 0.03), better appointment scheduling (β = -0.1, p = 0.8), and less patient waiting time (β = 0.7, p < 0.01). In conclusion, Lebanon has a high standard of outpatient care that is mainly influenced by the doctor-patient relationship rather than financial incentives.